Growth and Yield of Melon (Cucumis melo L.) at Various Doses of Bokashi Organic Fertilizer from Rice Straw Agricultural Waste - Maruapey, Ajang; Soekamto, Mira Herawati (Agrikan Jurnal Agribisnis Perikanan, 2022)
Melon has a high economic value because of its sweet, fresh fruit taste and high vitamins and carbohydrates to improve people's nutrition. The purpose of this study was to determine the effect of organic fertilizer bokashi rice straw on the growth and yield of melons. The research was conducted on farmers' land, Matalamagi Village, East Sorong District, Sorong City, West Papua. The research was conducted from January to March 2021. The variables observed were when shoots appeared, plant height, number of leaves at flowering age, harvest age, number of fruit plants, number of fruit plots, fruit circumference, and fruit weight. The research data were analyzed by means of variance (ANOVA), if there was a significant difference, then continued with the LSD (Least Significance Difference) test at the 5% level. The results showed that the application of organic fertilizer bokashi rice straw had a significant effect on the character of the components of growth and yield of melon plants. Treatment with a dose of organic fertilizer bokashi rice straw (j2) 10 t/ha or 4.50 kg/plot resulted in the highest TT at 2 weeks old (21.08) cm and 6 weeks old (87.06 cm), JD (7.17 strands). ), UB (27.79 days). Meanwhile, increasing the dose of organic fertilizer bokashi rice straw (j3) 15 t/ha or 6.75 kg/plot resulted in JBT (1.75 pieces), JBP (20.88 pieces), LB (42.53 cm) and BB (1 ,8 kg).